EMBR-07. MYC BUT NOT MYCN GENERATES AGGRESSIVE GROUP 3 MEDULLOBLASTOMA BY ARF PATHWAY SUPPRESSION. (1st June 2021) - Mainwaring, Oliver; Weishaupt, Holger; Hutter, Sonja; Zhao, Miao; Rosén, Gabriela; Breinschmid, Laura; Verbaan, Annemieke; Sundström, Anders; Annusver, Karl; Kasper, Maria; Swartling, Fredrik
Abstract: Medulloblastoma (MB), the most common malignant pediatric brain tumor, often harbor MYC amplifications and arise in the presence of a functional p53 suppressor protein. To elucidate the mechanism behind this inexplicable tumor development we generated an inducible, immunocompetent transgenic mouse model of MYC-driven MB. Tumors driven from the glutamate transporter promoter molecularly resembled aggressive Group 3 MB driven by an enriched photoreceptor program. They developed embryonically in a monoclonal fashion in the presence of a functional unmutated p53 gene. Compared to MYCN-expressing MB driven from the same promoter, we discovered pronounced silencing of the ARF suppressor upstream of p53. We similarly found significant methylation of the ARF promoter in MYC-amplified as compared to MYCN-amplified human MB samples. While MYCN-driven tumor malignancy was more sensitive to ARF depletion, it dramatically increased metastatic spread of MYC-driven tumors. DNMT inhibition could restore ARF levels in MYC-expressing tumors but did not show any therapeutic advantage in tumors in vivo. Computational modeling suggested the HSP90 protein to act as a more specific target and ARF could indeed be restored by the HSP90 inhibitor onalespib that promoted increased survival in our inducible animal model suggesting that HSP90 inhibition could be potentially used in patients affected by MYC-driven ARF-silenced cancer.